Genomic evidence for homoploid hybrid speciation between ancestors of two different genera - Zefu Wang; Minghui Kang; Jialiang Li; Zhiyang Zhang; Yufei Wang; Chunlin Chen; Yongzhi Yang; Jianquan Liu (Nature Communications, 2022)
Carpinus fangiana exhibits intermediate morphology between C. viminea and Ostrya rehderiana. Here, the authors report that Carpinus sect. Distegocarpus likely originate through homoploid hybrid speciation (HHS) during the early divergence between Carpinus and Ostrya through genomic analyses.